Warming up through buildings and roads: what we know and should know about the urban heat island effect on bees - Polidori, Carlo; Ferrari, Andrea; Ronchetti, Federico; Tommasi, Nicola; Nalini, Elia (Frontiers in Bee Science, 2023)
Urbanization leads to higher temperatures within cities compared with the surrounding non-urban areas (Urban Heat Island (UHI) effect). Very little is known about the impacts of the UHI effect on bees, despite the importance of temperature on many aspects of bees' life suggests that these may be not negligible. Here, we aimed to highlight how the UHI effect could impact relevant functional traits of bees in cities, proposing several ad-hoc hypotheses for traits little or not yet investigated, based on what we know from non-urban studies. The UHI effect was shown to influence bee body size, generally tending to reduce it in cities. Urban temperature may also affect wing morphology, and thus overall flight morphology parameters. Individuals may be brighter in cities. Ommatidial size and the number of antennal thermo-receptors may decrease in cities. Higher proportions of alkanes and longer main carbon chain length are expected in the cuticular hydrocarbon (CHC) profiles of urban bees to face higher desiccation risk. Stress biomarkers can occur at greater concentrations in cities. Specific bacteria in the bee gut may occur at lower abundances. Warm urban temperatures may impact the life cycle of pathogens by reducing their proliferation. Aggression levels may be increased and eusocial species may present more worker phases per year due to the UHI effect. All the proposed impacts could be likely more visible in solitary and primitively eusocial bee species, which are those suspected to have a more limited dispersal ability. Comparative studies would help testing properly for these hypotheses.